Gonadotrophin‐releasing hormone agonist combined with high‐intensity focused ultrasound ablation for adenomyosis: a clinical study. (30th August 2017) - Guo, Y; Duan, H; Cheng, J; Zhang, Y
Tweetable abstract: A combination of HIFU with GnRH‐a in the treatment of adenomyosis significantly decreased serum CA125 levels, uterine and adenomyotic lesion volumes, dysmenorrhoea scores, and menstrual blood volumes. Abstract : Objectives: This study was to investigate the clinical efficacy of a gonadotrophin‐releasing hormone agonist (GnRH‐a) combined with high‐intensity focused ultrasound (HIFU) ablation treatment for adenomyosis. Design: A non‐randomized prospective study. Setting: Gynaecological Minimally Invasive Centre in a single hospital. Population: Patients with adenomyosis. Methods: Seventy‐nine patients with adenomyosis were enrolled, including 55 patients in the control group treated with only HIFU and 24 patients in the study group treated with GnRH‐a combined with HIFU. All the patients follow up 6 months after the HIFU procedure. The related parameters in the two groups were assessed before and 3 months as well as 6 months after treatment including serum levels of tumor marker and cytokine, volumes of uterine, adenomyotic lesion, and menstrual blood, as well as dysmenorrheal scores. Main outcome measures: Differences between the group treated with HIFU alone and the group treated with GnRH‐a combined with HIFU. Results: Before HIFU treatment, no significant difference was observed in serum levels of CA125, CA19‐9, and interleukin‐6 (IL‐6), the volumes of uterine, adenomyotic lesion, and menstrual blood, as well as dysmenorrhea scores between the two groups. ( P  > 0.05). The serum CA125 levels significantly decreased in both groups after HIFU, but the serum CA125 levels in the study group were still significantly lower than those in the control group ( P  < 0.05). The volume of uterine and adenomyotic lesion significantly decreased in both groups after HIFU procedure, and decreased even more in the study group 3 and 6 months after treatment ( P  < 0.05). Dysmenorrhea scores and menstruation volumes significantly decreased in both groups after HIFU treatment. Moreover in the study group were significantly lower than those in the control group after 3 and 6 months ( P  < 0.05). No significant difference was observed in the rate of adverse effects between the two groups. Conclusions: The short‐term follow‐up results indicate that the combination of GnRH‐a and HIFU treatment significantly decreased serum CA125 levels, volumes of uterine, adenomyotic lesion and menstrual blood, as well as dysmenorrhea scores, and improved the clinical outcomes compared with the HIFU ablation alone in patients with adenomyosis. However, the further follow‐up is needed to explore the long‐term effects. Tweetable abstract: A combination of GnRH‐a with HIFU in the treatment of adenomyosis significantly decreased serum CA125 levels, uterine and adenomyotic lesion volumes, dysmenorrhea scores, and menstrual blood volumes.